Implementation Of Management Policy Of Rental Flats (RUSUNAWA) In Bengkulu City - Indarti, Sri; Sari, Sinta Permata (GAYAKU PUBLISHER, 2024)
Rumah susun sewa (Rusunawa) is a multi-storey building built to address housing needs in an area. Rusunawa Bengkulu is the first flat in Bengkulu City built by the Ministry of PUPR through the Bengkulu City government, and managed by the Bengkulu City Housing and Settlement Office (Perkimtan). This flat is intended for the low-income Bengkulu community or MBR. The purpose of this research is to find out how the implementation of policies in the management of Rusunawa Bengkulu. The research method is descriptive with a qualitative approach. Data obtained through the process of observation, interviews and documentation. The overall research results show that the management of Rusunawa Bengkulu is not running well, because there is still a lot of damage to the flat that is not repaired, it is due to the absence of a budget given by the City Government to the Perkimtan Office to repair the damage in Rusunawa Bengkulu.